PLASTIC OF CHOLEDOCHUS BY WALL SEGMENT OF GALLBLADDER - Dubinin, S.I.; Malik, S.V.; Ulanovska-Tsyba, N.A.; Lavrenko, D.O.; Ryabushko, O.B.; Perederii, N.O. (World of Medicine and Biology, 2016)
In this work, under conditions of experimental researches, the model of the common bile duct plastic in emergency situation using wall segment of gallbladder with further hepatotomy on external drains has proposed. The results of experimental studies may be appropriate for use in the clinic.
Keywords: cholecystitis; choledochus plastic defect